AN ENGLISH SYLLABUS DESIGN FOR THE TENTH GRADE STUDENTS OF TOURISM (HOTEL ACCOMODATION DEPARTEMENT) - ., Kurniati (JURNAL SMART, 2016)
The new curriculum of 2013 regulates 90 minutes in a week to learn English at the first year students of vocational school from 270 minutes before. Therefore, the students become have lack of exposure to the language. Besides, the syllabus is still general, it did not focus on vocational school department. Because of that, the researcher conducted this research. The data sources that used in this research are observation, interview, test and documentation. First was interview which given to present and alumni of State Vocational School 57 Jakarta, stakeholders and hotel staffs. Second, observation was conducted at hotel as a real situation of workplace. Third test was given to the students to know the learner lack of language. Fourth, documentation was taken by recording the interviewing data and implementation syllabus process in the class.The result of this research found that new English syllabus related to job field. From implementation of samples unit found that 67.5% the lesson was understandable, 80% interesting, 75% autonomous and 65% satisfactory. Whereas the result did not reach 100% satisfactory, but it proved that the English syllabus designed was successful.Keywords: Autonomous, Designing, Need analysis, Syllabus and Implementation.